The Effect of Green Finance on Bank Value: a Case from Indonesia - Baharudin, Bany Sutan; Arifin, Zaenal (Journal of Social Research, 2023)
Sustainability is currently a concern for many parties, including banks. The Bank began to consider whether the proposed funding would be allocated for projects that do not conflict with natural sustainability. This is known as green finance. This study aims to determine whether the implementation of green finance affects the value or performance of the bank. The research sample is go-public banks in Indonesia for the period 2019 – 2021. This study found that 70.93% of banks implement green finance. This study found that the implementation of green finance has a positive effect on firm value when the proxy for firm value is Tobin Q. However, when the proxy for firm value is the Price Earnings Ratio, Earnings per share, and Stock Return, then the implementation of green finance has no effect on company value. This study also found that the effect of green finance on firm value was more evident in banks in the KBMI 4 group. Of the four models used in this study, three models found a significant positive effect, namely the TobinQ, Stock Return, and EPS models. only in the PER model did not show any effect.